Assessing and reducing the environmental impact of dairy production systems in the northern US in a changing climate. (August 2021) - Veltman, Karin; Rotz, C. Alan; Chase, Larry; Cooper, Joyce; Forest, Chris E.; Ingraham, Peter A.; Izaurralde, R. César; Jones, Curtis D.; Nicholas, Robert E.; Ruark, Matthew D.; Salas, William; Thoma, Greg; et al.
Abstract: CONTEXT: To meet the nutritional and environmental needs of a growing population, dairy producers must increase milk production while minimizing the farm-gate environmental impact and adapting to the effects of climate change. OBJECTIVE: Here we comprehensively assess the effects of climate change on the environmental performance and productivity of three typical US dairy farms, and evaluate the potential benefits of adaptation strategies and implementation of Beneficial Management Practices (BMPs) for mitigating these effects and the potential increases in environmental impact. METHODS: Using the Integrated Farm System Model (IFSM), we predicted the productivity and environmental impact of these baseline farms under current emission scenarios and climate projections of 6 general circulation models (GCM), for high and low emission scenarios. We simulated farm-specific BMPs for current and future climate conditions for both unadapted and 'adapted' field cultivation plans, based on experiences from other climate locations. Finally, the IFSM predictions were compared to those of two other process-based models to test result robustness. RESULTS AND CONCLUSIONS: We find that the environmental impact of the three northern US dairy farms (New York, Pennsylvania, and Wisconsin) generally increases by mid-century, if no mitigation measures are taken. Overall, feed production is maintained, as decreased corn grain yields are compensated by increased forage yields. Adoption of farm-specific Beneficial Management Practices can substantially reduce the GHG emissions and nutrient losses from dairy farms under current climate conditions and stabilize the environmental impact in future climate conditions, while maintaining farm productivity (milk and feed production). A comparison of three models corroborates the estimated reductions in methane and ammonia emissions associated with BMPs, as well as the relative trend in P-loss reduction. SIGNIFICANCE: This study provides a holistic assessment of the impacts of climate change on dairy production systems focusing on both feed production and environmental impacts. It demonstrates the interest of BMPs to both reduce GHG emissions and contribute to more resilient farming systems in a changing climate. Graphical abstract: Unlabelled Image Highlights: Absent mitigation measures, the environmental impact of northern US dairy production increases by 2050 Feed production is maintained as reduced corn grain yields are compensated by increased forage yields Adoption of farm-specific BMPs can stabilize the environmental impact in future climate conditions Farm productivity (milk and feed production) in future climate conditions is maintained under BMP implementation